Preservation of Alveolar Ridge after Preimplantation Tooth Extraction (A Review) - R. Jurkovič; P. Stanko (Czech Dental Chamber, 2006)
The aim of the athors was to provide and represent different possibilities offered by materials for substitution of bones used after tooth extraction as a prevention of resorption of alveolar process. The use of autogenous bone, allogenic and xenogenic grafts, alloplastic and synthetic materials is described. Membranes used for controlled bone regeneration in the described indication are described. The aim of preserving the alveolar ridge is to preserve ideal anatomical conditions, which does not only provide the correct function, but also adequate aesthetic of prosthetic rehabilitation.